Dampak Keterlibatan Ayah dalam Pengasuhan Remaja: Sebuah Studi Literatur - Fauzana, Kurnia (Happiness: Journal of Psychology and Islamic Science, 2023)
Parents have a responsibility for the upbringing of their children. Both of parents have an important role related to the growth of children. The purpose of this study was to find what are the impact of father involvement on adolescents in parenting. This study uses a literature review method with a traditional type of review. The criteria for the articles used are in the Indonesian language, are complete research articles, have a publication year range from 2017 to 2022, and the research subjects are adolescents. The number of articles analyzed was 9 articles. The database used is Google Scholar and uses the keywords parenting, father involvement, and adolescent according to the topic of discussion. The results of the study show that the involvement of the father can have an effect on adolescents. The involvement of fathers in parenting can have impact on self-control, self-concept, emotional maturity, social adjustment, juvenile delinquency, psychological well-being, life satisfaction, self-confidence, and self-esteem in adolescents. Parenting performed by fathers can be influenced by education level, age, cohabiting with the child, occupation, and the number of hours working.